The Effect Of Hypnoteaching On The Habit Of Using Harsh Language In Elementary School Grades 4-6 At Rumah Belajar Ceria - Yuza, Okta Della; Martini, Sri; Pastuty, Rosyati (Poltekkes Kemenkes Palembang, 2025)
At school age there is an emotional upheaval that is inseparable from environmental influences. At this time children also experience growth and development. Development that experiences obstacles will lead to forms of child behavior with angry reactions in the form of verbal actions, such as speaking harshly. If this habit of speaking harshly is allowed to continue, then this habit will develop into verbal bullying. Hypnoteaching is one of the hypnotherapy techniques that can help change children's behavior and prevent and overcome problems that may occur because it emphasizes more on giving suggestions in repetition (repetition) so that children will feel confident that they are good children. The belief will make the children leave the bad habits. To find out the effect of hypnoteaching on the habit of using harsh language in elementary school children in grades 4-6 at Rumah Belajar Ceria in 2024. This study used true experimental method with randomized pretest-posttest group design. This research was conducted in October 2023-April 2024. The number of samples in this study were 36 children who were actively studying at Rumah Belajar Ceria. Analysis of research data using nonparametric tests Wilcoxon with Independent Sample T-Test. The average habit of using harsh language before being given hypnoteaching was in the mild category, while the average knowledge of mothers after being given the intervention was in the category of not speaking harshly. The results of the research show that there is an influence of hypnoteaching on the habit of using harsh language in elementary school in grades 4-6 at Rumah Belajar Ceria in 2024 (ρ=0.000<0.05). There is an effect of hypnoteaching on the habit of using harsh language in elementary school children in grades 4-6 at Rumah Belajar Ceria in 2024.